Tax buyouts - Marco Del Negro; Fabrizio Perri; Fabiano Schivardi (Federal Reserve Bank of New York, 2010)
The paper studies a fiscal policy instrument that can reduce fiscal distortions, without affecting revenues, in a politically viable way. The instrument is a private contract (tax buyout), offered by the government to each individual citizen, whereby the citizen can choose to pay a fixed price up front in exchange for a given reduction in her tax rate for a prespecified period of time. We consider a dynamic overlapping-generations economy, calibrated to match several features of the U.S. income and wealth distribution, and show that, under simple pricing, the introduction of the buyout is revenue neutral and at the same time can benefit a significant fraction of the population and lead to sizable increases in labor supply, income, consumption, and welfare.
Keywords: E62; H21; 330; Taxes; private information; distortions; Öffentliche Finanzwirtschaft; Öffentliche Einnahmen; Steuerpolitik; Steuerbelastung; Lebenszyklus; Overlapping Generations; Wohlfahrtsanalyse; USA